HE4 as a serum biomarker for the diagnosis of pelvic masses: a prospective, multicenter study in 965 patients - Elena Ioana Braicu; Catherine Linn Krause; Uwe Torsten; Herbert Mecke; Rolf Richter; Lars Hellmeyer; Malgorzata Lanowska; Bodo Müller; Elisa Koch; Janine Boenneß-Zaloum; Kerstin Ames; Radoslav Chekerov; et al. (BMC Cancer, 2022)
Highlights • Serum biomarkers can help to distinguish benign from malignant pelvic masses • We evaluated the diagnostic value of adding HE4, CA125 and ROMA to ultrasound for detecting ovarian cancer • In stage III and IV ovarian cancer all three biomarkers showed excellent performance • ROMA and HE4 performed better than CA125 in the differential diagnosis of ovarian cancer and endometriosis